The Impact Of Employees’ Training Programme On The Performance Of Small Medium Enterprises In Northern Malaysia - LIM, KHANG GUAN (2004)
The trend towards global market orientation and trade liberalization requires the SMEs in Malaysia to increasingly emphasize on compressed product life-cycles, enhancing quality improvements, and towards product and process innovations. Employees’ training is one of the factors that have the effect on SMEs’ performance. Thus, the objective of this study is to identify the impact of SMEs’ training programme on SMEs’ performance.